PROFESYONEL VE AMATÖR FUTBOLCULARIN PSİKOLOJİK YILDIRMAYA (MOBBİNG) MARUZ KALMA SIKLIKLARININ ARAŞTIRILMASI - KIZILKOCA, MUSTAFA (Fırat Üniveristesi, 2012)
Bu çalışmada, futbolcuların psikolojik yıldırmaya maruz kalma sıklıklarını belirlemek, Profesyonel ve amatör olarak futbol oynamanın psikolojik yıldırmaya maruz kalma sıklıklarını etkileme durumlarını ortaya koymak ve futbolcuların oynadıkları lig ve demografik özellikleri ile psikolojik yıldırılmaya maruz kalma sıklıkları arasındaki ilişkiyi saptamak amaçlanmıştır.Araştırmaya Türkiye Futbol Federasyonu kulüplerinde mücadele eden futbolculardan tesadüfi örneklem yöntemi ile belirlenen 128 futbolcu gönüllü olarak katılmıştır. Çalışmaya katılan futbolcuların gerekli bilgileriyle birlikte demografik özelliklerini belirlemeye yönelik bir bilgi formu hazırlanmıştır. Ayrıca futbolcuların psikolojik yıldırmaya maruz kalma sıklıklarını belirlemek için "Sporcular için Mobbing (Yıldırma) Envanteri" kullanılmıştır.Araştırma verilerinin değerlendirilmesinde SPSS istatistik paket programı kullanılmış olup anlamlılık düzeyi P<0.05 olarak alınmıştır. İstatistikî yöntem olarak; frekans, yüzde dağılımları, bağımsız gruplar için t-testi ve tek yönlü varyans analizi (ANOVA) kullanılmıştır. Psikolojik yıldırma ve demografik arasındaki ilişkinin düzeyini ve yönünü belirlemek için ise korelasyon analizi uygulanmıştır.Araştırmamızda elde edilen demografik özelliklerine göre yaş, eğitim, sporculuk yılı ve takım kategorisi bakımından incelendiğinde profesyonel ve amatör futbolcuların psikolojik yıldırmaya maruz kalmadıkları, İstatistikî analizlere baktığımızda anlamlı farklılaşmanın olmadığı bulunmuştur.Anahtar Kelimeler: Psikolojik Yıldırma, Futbolcu, Amatör, Profesyonel

THE STUDY OF THE FREQUENCY OF EXPOSURE TO PSYCHOLOGICAL DEMORALIZATION (MOBBING) FOR THE PROFESSIONAL AND AMATEUR FOOTBALLERSThe purpose of this study is to define the frequency of exposure to psychological demoralization for the footballers, to present the effects of playing football professional and amateur on the frequency of exposure to psychological demoralization and to determine the relationship between the league in which the footballers are playing, their demographical characteristics and the frequency of exposure to psychological demoralization.128 footballers determined through the method of random sampling from Turkish Football Federation clubs participated in the study voluntarily. An information form intended to determine the necessary information and demographical characteristics of the footballers participating in the study was prepared. In addition, ?Mobbing (Demoralization) Inventory for the Athletes? was used to determine the frequency of exposure to psychological demoralization for the footballers.SPSS statistics packaged software was used in the evaluation of survey data and P<0.05 has been taken as significance level. Frequency, percentage distributions, t-test for independent groups and unilateral variance analysis (ANOVA) were used as statistical method. Correlation analysis was applied to determine the level and direction of the relationship between psychological demoralization and demographics.According to the demographic features acquired through the survey, it has been discovered that when analyzed in terms of age, education, sportsmanship year and team category, professional and amateur footballers aren?t exposed to psychological demoralization. It has been discovered that there is no meaningful differentiation by looking at the statistical analyses.Keywords: Mobbing, Soccer, Amateur, Professional
The study of the frequency of exposure to psychological demoralization (mobbing) for the professional and amateur footballers
Keywords: Spor